Photo-crosslinking Permanent Optical Storage Devices using Biocompatible Kojic Acids - Hegde, Gurumurthy; Gan, Siew Mei; Shu, Ting Chua; Yuvaraj, A. R.; M. M., Yusoff; Zainab, Ngaini; Ainaa Nadiah, Abd Halim; Carolynne Sie, Zie Wei (2014)
Biocompatible kojic acids incorporated in azodye molecules were studied with the illumination of UV light. Study revealed the novel photo crosslinking effect where kojic acidazodye molecules crosslink themselves with the light which allow molecules to create permanent optical storage devices. Obtained results are very useful for the electronic industry because of cost effective approach and easy to crosslink nature.